2007
DOI: 10.1523/jneurosci.2199-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Nicotine Cell Specifically Upregulates Functional α4* Nicotinic Receptors: Basis for Both Tolerance in Midbrain and Enhanced Long-Term Potentiation in Perforant Path

Abstract: Understanding effects of chronic nicotine requires identifying the neurons and synapses whose responses to nicotine itself, and to endogenous acetylcholine, are altered by continued exposure to the drug. To address this problem, we developed mice whose ␣4 nicotinic receptor subunits are replaced by normally functioning fluorescently tagged subunits, providing quantitative studies of receptor regulation at micrometer resolution. Chronic nicotine increased ␣4 fluorescence in several regions; among these, midbrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
321
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 248 publications
(357 citation statements)
references
References 100 publications
(174 reference statements)
35
321
0
1
Order By: Relevance
“…Consistent with previous descriptions that report that more then 99% of TH cells contain alpha4 (Arroyo-Jimenez, et al, 1999;Nashmi et al, 2007), a high level of co-incident labeling was observed. However there was also labeling for alpha4 present in non-TH cells, consistent with the presence of alpha4 within some interneurons in the substantia nigra (Nashmi et al, 2007). Subsequently, the distribution in the DR was examined.…”
supporting
confidence: 92%
“…Consistent with previous descriptions that report that more then 99% of TH cells contain alpha4 (Arroyo-Jimenez, et al, 1999;Nashmi et al, 2007), a high level of co-incident labeling was observed. However there was also labeling for alpha4 present in non-TH cells, consistent with the presence of alpha4 within some interneurons in the substantia nigra (Nashmi et al, 2007). Subsequently, the distribution in the DR was examined.…”
supporting
confidence: 92%
“…Adult (2.5-4 months old) male wild-type or ␣4-YFP knock-in mice (Nashmi et al, 2007) with C57BL/6J background were used. The ␣4-YFP knock-in mice also co-expressed a hemagglutinin (HA) epitope tag.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining for HA on YFP-tagged ␣4* nAChRs (Nashmi et al, 2007) was achieved by immersing fixed brain sections in 0.3% H 2 O 2 for 15 min followed by overnight incubation in PBS containing rabbit anti-HA antibodies (1:1000, Sigma). Sections were then incubated for 2 h in PBS containing biotin-conjugated anti-rabbit antibodies (1:1000, Vectastain Elite kit, Vector Labs), followed by incu- Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations